2012 IEEE International Ultrasonics Symposium 2012
DOI: 10.1109/ultsym.2012.0673
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of ultrasonic guided waves using the Scaled Boundary Finite Element Method

Abstract: The formulation of the Scaled Boundary Finite Element Method is applied for the computation of dispersion properties of ultrasonic guided waves. The cross-section of the waveguide is discretized in the Finite Element sense, while the direction of propagation is described analytically. A standard eigenvalue problem is derived to compute the wave numbers of propagating modes. This paper focuses on cylindrical waveguides, where only a straight line has to be discretized. Higher-order elements are utilized for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In previous work, 9,32,43 detailed formulations have been presented to compute dispersion properties of guided waves in plates, axisymmetric structures, and general threedimensional waveguides, respectively. For all geometries, the waveguide's cross-section is discretized in the finite element sense, while the direction of wave propagation is described analytically.…”
Section: A Waveguide With Stress-free Surfacesmentioning
confidence: 99%
“…In previous work, 9,32,43 detailed formulations have been presented to compute dispersion properties of guided waves in plates, axisymmetric structures, and general threedimensional waveguides, respectively. For all geometries, the waveguide's cross-section is discretized in the finite element sense, while the direction of wave propagation is described analytically.…”
Section: A Waveguide With Stress-free Surfacesmentioning
confidence: 99%
“…These methods include the Finite Element Method (FEM) [16,17], Finite Difference Method (FDM) [18][19][20], Finite Volume Method (FVM) (also known as Finite Integration Technique (FIT) [21]), and Boundary Element Method (BEM) [9,22]. Studies have shown that ultrasonic scattering or attenuation can be used to characterize poly-crystalline micro-structures and to localize flaws [17,23,24]. Establishing the relationship between ultrasonic scattering/attenuation and material parameters enables reliable and high-quality material testing [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the experimental ToA value was measured at 13.10 [µs], while the corresponding numerical value was recorded as 13. 23 [µs], thus resulting in a small relative error of 0.983%. The observed consistency between the experimental and numerical results indicated a reliable correspondence between the physical measurements and the numerical modeling.…”
mentioning
confidence: 99%
See 2 more Smart Citations